(untitled) - Payne, Robert (New York, 1967)
The Russian revolutionaries have profoundly affected our age. For nearly a hundred years from 1825 to 1917, they hammered at the gates of the autocracy, attempting to destroy the Tsar and all his works, employing their small weapons against the entrenched power of an absolute monarchy. Their punishment was to be thrown into the Peter and Paul Fortress in St. Petersburg, where they were tortured and sometimes beaten to death, or left to rot in the silence of their cells...
Keywords: Revolutionaries; Soviet union